150 YEARS OF THE SOKOL GYMNASTICS IN CZECHOSLOVAKIA, CZECH AND SLOVAK REPUBLIC - Anton Gajdoš; Maria Provaznikova; Stephen J. Banjak (Science of Gymnastics Journal)
Gymnastics in Slavic countries started in 1862 with Sokol club in Prague. Leader Miroslav Tyrš made strong organisation within Austro Hungary imperia, which competed also at Olympic Games under Bohemia name. After World War I Czech and Slovak nations joint in new state Czechoslovakia. Time between world wars was most succesfull time with many gold medals at Olympic games and Word Championships. After the second world war communist party took a leading role in gymnastics development with highlight on women side; Vera Caslavska is the best athlete of this time. After velvet revolution Czechoslovakia split into two countries Czech and Slovakia. Gymnastics tradition continues again under Sokol brand name.